Multi‐level Assessment of Scientific Content Knowledge Gains Associated with Socioscientific Issues‐based Instruction - Klosterman, Michelle L.; Sadler, Troy D. (International Journal of Science Education, 2009)
This study explored the impact of using a socioscientific issue (SSI) based curriculum on developing science content knowledge. Using a multi‐level assessment design, student content knowledge gains were measured before and after implementation of a three‐week unit on global warming (a prominent SSI) that explored both the relevant science content and the controversy surrounding global warming. Measures of student content knowledge were made using a standards‐aligned content knowledge exam (distal assessment) and a curriculum‐aligned exam (proximal assessment). Data were collected from 108 students enrolled from two schools. Quantitative analysis of the distal assessment indicated that student post‐test scores were statistically significantly different than their pre‐test scores (F = 15.31, p<0.001). Qualitative analyses of student responses from the proximal assessment indicated that students, on average, expressed more accurate, more detailed, and more sophisticated understandings of global warming, the greenhouse effect, and the controversy and challenges associated with these issues following the three‐week unit. Combined results from the proximal and distal assessments explored in this study offer important evidence in supporting the efficacy of using SSI as contexts for science education. In addition to a discussion of the components of an SSI‐based curriculum, this study provides support for the use of SSI as a context for learning science content.